INDONESIAN MUSLIM VALUES, PRACTICES, TERMI-NOLOGIES AND SYMBOLS REPRESENTED IN RICHARD LEWIS THE FLAME TREE - Rosyida ekawati (Soegijapranata Catholic University, 2014)
Islam is one of the official religions in Indonesia, with its adherents constituting the majority of the population. Muslims in Indonesia have their own values in accord with the teachings of Islam, practiced in their daily life and adapted to the culture. Historically, Islam in Indonesia, particularly in Java, was introduced through acculturation. Todays ceremonies accompanying the implementation of Islamic teachings is an example of the daily practice that characterizes Muslims being influenced by the local culture. Moreover, in their everyday life, Muslims in Indonesia often use Islamic terminologies and Arabic words. They include greetings and expressions for starting as well as ending an activity. As for Islamic symbols, the star and the crescent on the top of the mosque dome or a Quranic verse put at home or in the workplace are typical representations, distinguishing the Muslims from adherents of other faiths.